Urbanization in a Globalized World: Reviewing Environmental Sustainability in Developing Countries - Kalsoom Zulfiqar; Ali Asad Sabir; Abdul Rehman Nawaz; Fatima Farasat (Население и экономика)
Climate change remains a critical issue worldwide, and balancing economic growth with sustainable development is of paramount importance. Our study explores the complex relationship between globalization, environmental sustainability, and urbanization in selected developing countries. By utilizing a simple panel regression technique and data from 40 developing countries from 1994 to 2018, the study examines how these factors influence environmental stability. We find that with a strong focus on environmental sustainability, economic growth can be enhanced. Additionally, we find that globalization, along with GDP per capita and access to electricity, significantly impacts environmental sustainability. Conversely, the effect of urbanization on environmental stability appears to be minimal.